1999
DOI: 10.3171/jns.1999.91.4.0547
|View full text |Cite
|
Sign up to set email alerts
|

Extracranial vertebral artery stent placement: in-hospital and follow-up results

Abstract: Vertebral artery stent placement is feasible in patients who have significant VA stenosis, with predictably good angiographically demonstrated and clinical results. The 6-month angiographically confirmed restenosis rate appears to be low, as does the clinical recurrence rate. This technique solves the problems of elastic recoil and the treatment of angioplasty-induced dissections. Further prospective comparison with medical preventive strategies is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
1
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(58 citation statements)
references
References 25 publications
2
52
1
3
Order By: Relevance
“…El éxito técnico se definió como una estenosis residual < 20% y se produjo en un 99,3% de los casos incluidos en esta revisión. El fallo del despliegue del stent se atribuyó a la tortuosidad importante del origen de la vertebral en 1 serie 22 . Se describieron casos aislados de desalojo o migración de stents 25,28,33 .…”
Section: Discusión Seguridad Y Viabilidad Técnicaunclassified
See 1 more Smart Citation
“…El éxito técnico se definió como una estenosis residual < 20% y se produjo en un 99,3% de los casos incluidos en esta revisión. El fallo del despliegue del stent se atribuyó a la tortuosidad importante del origen de la vertebral en 1 serie 22 . Se describieron casos aislados de desalojo o migración de stents 25,28,33 .…”
Section: Discusión Seguridad Y Viabilidad Técnicaunclassified
“…Failure of stent deployment was attributed to severe tortuosity of vertebral origin in 1 series. 22 There were isolated reports of stents that dislodged or migrated. 25,28,33 A total of 7 cases described stent fracture identified at follow-up angiography.…”
Section: Safety and Technical Feasibilitymentioning
confidence: 99%
“…VA angioplasty was first performed in 1980 by Sundt et al Numerous clinical studies conducted since then have indicated the importance of angioplasty and stenting in the treatment of vertebrobasilar atherosclerotic disease (13)(14)(15)(16)(17). Technical success depends on the development of materials used in endovascular treatment, the degree of stenosis, the vascular tortuosity, and the experience of the neuroradiologist who performs the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, stents cut from a tube were used to prevent breakage in the orifice lesions due to the angulation of VA with subclavian artery, while balloon expandable stents are used today. Drug-releasing stents may also reduce restenosis in this region where restenosis is more prominent (5,14,19). VA balloon angioplasty and anticoagulant and antithrombotic treatment protocols as a medical therapy after stenting are the standard applications indicated in the literature (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Available data on such interventions are derived from small case series. [85][86][87][88] Ongoing clinical trials are addressing the role of endovascular treatment for these indications.…”
mentioning
confidence: 99%